Variasi Sapaan Ragam Akrab dan Ragam Santai Masyarakat Melayu Jambi dalam Komunikasi Verbal (Kajian Sosiolinguistik) - Ade Rahima (Universitas Batanghari Jambi, 2021)
The purpose of this research is to describe the familiar and relaxed variety of speech greetings in the Malay community of Jambi. The focus of the research is related to 3 things, namely: 1) the forms of various forms of addressing familiar and casual types of discourse, 2) the factors behind the variations in addressing variations in various discourses, and 3) sentence patterns that contain variations in addressing familiar and casual types of discourse. in the verbal communication of the Jambi Malay community. This research is a qualitative research with a sociolinguistic approach. Field data collection uses ethnographic methods. Ethnographic techniques used include participatory observation, in-depth interviews, introspection, and domine analysis. Primary data comes from 8 informants and secondary data comes from documents. Data were analyzed based on socio-cultural and situational factors. Based on the results and discussion, it can be concluded that: 1) The forms of variation of greetings in the verbal communication of the Jambi Malay community are in the familiar and casual types. Forms of greeting used include pangilan kesanyangan, name abbreviations, intimate calls and special calls outside the language. This variation is found in verbal communication between family members whether they are older, the same age, or less. The variety of friendly and casual types of greetings outside of family relationships occurs in close friends or close friends, usually using special calls. 2) The factors that cause the use of familiar and casual types of greetings in verbal communication are determined by the factor of the proximity of the speaker and speaker relationship, the situation of speech and the topic of speech 4) The sentence pattern of the familiar variety tends to be Subject-Predicate (SP) while the casual variety Object (PO).